Efeitos da paisagem nos polinizadores e na polinização: revisão sistemática da literatura - Rocha, Ana Carolina (2023)
The modifications to natural environments not only affect the landscape structure but also impact pollinators, pollination, and plant-pollinator interactions. The maintenance and conservation of pollination and these interactions influence social and economic sustainability goals, given the impact of pollination on other species that mediate relevant ecological processes such as climate regulation, seed dispersal, nutrient cycling, among others. Therefore, the objective of this study is to provide a synthesis of the impact of landscape structure on the ecosystem service of pollination through a systematic literature review covering the period from 2011 to 2021. Despite recent empirical information on the subject, it is not systematically organized, making it necessary to synthesize the available knowledge in recent years. To conduct the systematic literature review, three fundamental stages were carried out: planning, implementation, and documentation. Clarivate Analytics' Web of Science and SciVerse Scopus databases were used for the selection of published studies. Search terms were defined using the boolean operator AND, as well as keywords such as Pollinator, Landscape, and Pollination. A total of 2,531 studies, written in English and Portuguese, were analyzed. Among these, 576 articles were selected based on their titles. After reading the abstracts, 342 articles remained to be read in full. Of these, 55 were excluded as review articles, modeling studies, meta-analyses, or for not meeting the criteria of this systematic review. The results obtained showed that resource availability and coverage of natural areas had a positive effect on bee diversity. On the other hand, areas near agricultural or urban coverage showed a greater negative impact on bee diversity. These findings support the hypothesis that modifications to the landscape structure affect the diversity of pollinator species. The obtained results will provide a deeper understanding of the topic, assisting in identifying specific landscape characteristics that can impact pollinator species. This, in turn, will help in making better-informed decisions and prioritizing conservation actions based on the particularities of each region or species.